Designing an Interactive Field Epidemiology Case Study Training for Public Health Practitioners - Nelson, Amy L.; Bradley, Lauren; MacDonald, Pia D. M. (Frontiers in Public Health, 2018)
Globally, public health practitioners are called upon to respond quickly and capably to mitigate a variety of immediate and incipient threats to the health of their communities, which often requires additional training in new or updated methodologies or epidemiologic phenomena. Competing public health priorities and limited training resources can present challenges in developed and developing countries alike. Training provided to front-line public health workers by ministries of health, donors and/or partner organizations should be delivered in a way that is effective, adaptable to local conditions and culture, and should be an experience perceived as a job benefit. In this review, we share methods for interactive case-study training methodologies, including the use of problem-based scenarios, role-play activities, and other small-group focused efforts that encourage the learner to discuss and synthesize the concepts taught. We have fine-tuned these methods through years of carrying out training of all levels of public health practitioners in dozens of countries worldwide.